A study of modified hermite polynomials - Khan, Mumtaz Ahmad; Khan, Abdul Hakim; Ahmad, Naeem (Pro Mathematica, 2011)
The present paper is a study of modied Hermitepolynomials Hn(x; a) which reduces to Hermite polynomialsHn(x) for a = e.